Factores determinates des comportamiento ético/no ético del empleado: Una revisión de la literatura - Pablo Ruiz Palomino; Carmen Ruiz Amaya (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2011)
In the literature on business ethics a large number of studies can be found with a focus on establishing comprehension frameworks concerning the factors which make an individual behave ethically or unethically. However, the models proposed up to the present moment are excessively generalists, as there are no specifications on those factors which are presented as more prominent in terms of influence according to the empirical literature. The purpose of this paper is to develop an explanatory model that in addition to allowing a better comprehension of the main factors influencing on the individual's ethical behaviour. For this aim we review the most significant contributions in the literature on this aspect and raise a series of theoretical propositions which define the explanatory model. Finally we present the discussion of the model, thus drawing a series of conclusions and proposing future lines for research.
Keywords: M1; M10; M14; 330; ethical/unethical behaviour; organizational ethics; individual characteristics context; explanatory model